FGB1 and WSC3 are in planta‐induced β‐glucan‐binding fungal lectins with different functions. Issue 3 (4th March 2019) - Wawra, Stephan; Fesel, Philipp; Widmer, Heidi; Neumann, Ulla; Lahrmann, Urs; Becker, Stefan; Hehemann, Jan‐Hendrik; Langen, Gregor; Zuccaro, Alga
Summary: In the root endophyte Serendipita indica, several lectin‐like members of the expanded multigene family of WSC proteins are transcriptionally induced in planta and are potentially involved in β ‐glucan remodeling at the fungal cell wall. Using biochemical and cytological approaches we show that one of these lectins, Si WSC3 with three WSC domains, is an integral fungal cell wall component that binds to long‐chain β 1‐3‐glucan but has no affinity for shorter β 1‐3‐ or β 1‐6‐linked glucose oligomers. Comparative analysis with the previously identified β ‐glucan‐binding lectin Si FGB1 demonstrated that whereas Si WSC3 does not require β 1‐6‐linked glucose for efficient binding to branched β 1‐3‐glucan, Si FGB1 does. In contrast to Si FGB1, the multivalent Si WSC3 lectin can efficiently agglutinate fungal cells and is additionally induced during fungus–fungus confrontation, suggesting different functions for these two β ‐glucan‐binding lectins. Our results highlight the importance of the β ‐glucan cell wall component in plant–fungus interactions and the potential of β ‐glucan‐binding lectins as specific detection tools for fungi in vivo .